Tools that guide the thesis and graduation project: the case of the handbooks and manuals the University of Cuenca-Ecuador (2010-2016) (Revista Electrónica Calidad en la Educación Superior, 2018)
A requisite before obtaining a professional degree in the different university course studies is the pre-graduate thesis o graduation project which, necessarily, is governed by parameters according to the requirements of the University. The current article takes as its point of departure the problem recognized in the research process and the development of graduation projects – low graduation rates, lack of writing skills, and dispersion of requirements – taking as a case of study the University of Cuenca (Ecuador) and the different faculties therein. The methodology and the main objective were to analyze the different mechanism that are used in each faculty (handbooks and manuals), through primary documents.